Reading comprehension performance of fourth year high school students of las pinas national high school, las pinas city (main campus) - Gonzales, Violeta M. (Manila : National University, 2009)
The present study offers an alternative solution to the problem besetting the public secondary schools throughout the country. Hence, it is significant for several reasons.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Survey type.
Includes bibliographical references.